Prevalence and determinants of underweight, overweight, and obesity among adolescent secondary school students in Dongola City, Northern Sudan in 2019 - Alzain, Mohamed Ali; Abdelaziz, Mohamed O.; Mustafa, Areej E.; Elsheikh, Mohamed (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescents comprise 1.2 billion of the world population. There is a worldwide increase in the prevalence of obesity and overweight among adolescents. This study aimed to determine the prevalence of underweight, overweight, and obesity among secondary school adolescents in Dongola city, North Sudan. Methods: A cross-sectional, school-based study was conducted among adolescents from 7 out of 11 schools in Dongola city in November 2019. Multistage sampling method was used besides ethical approval and informed consent were taken. Data was collected through questionnaire, weight and height of each participant were measured, body mass index was calculated and the World Health Organization (WHO) (5-19 years) reference chart was used to determine underweight, overweight, and obesity. Chi-square test and multinomial logistic regression were performed to determine factors associated with underweight, overweight, and obesity. Results: The study included 695 students with 397 (57.1%) males. The prevalence rates of underweight, overweight, and obesity were 12.2%, 15.7% and 5.2% respectively. Male students had more than twice times (OR=2.37; 95%CI=1.29-4.37) likely to be underweight. Students with family history of obesity had almost twice and two and half times (OR=1.78; 95% CI: 1.15-2.76) and (OR=2.46; 95% CI: 1.21-4.98) more likely to have overweight and obesity respectively. Students living in urban areas had thirteen times (OR=13.0; 95% CI: 1.76-0.96.7) more likely to be obese. Conclusions: The prevalence rates of underweight, overweight, and obesity are high compared to primary school children in Northern State. There is a need to strengthen the school health program and further studies involving rural and urban schools are recommended.